Fungsi Pengawasan dalam Pembuatan Sumur Bor di Selagai Lingga, Lampung Tengah - Setiawan, Andi; Wardhana, Yuditya (Jurnal Analisis Sosial Politik, 2021)
Clean water is one of the basic human needs, both for drinking water, MCK (bathing, washing, toilet), industrial needs and other needs. However, the current problem, especially in big cities, is that the need for clean water is often not met properly, even though its role for the community is so large that a person is willing to sacrifice time, energy and even money to be able to meet the need for clean water. In an effort to control the drilling of wells by the community independently to meet household clean water needs, the Regional Government of Central Lampung Regency issued Regional Regulation of Central Lampung Regency Number 16 of 2012 concerning Groundwater Management. In the Central Lampung Regency Regional Regulation Number 16 of 2012 it is conveyed that the construction of drilled wells is groundwater extraction, so that it must meet technical standards so as not to disturb the ecosystem and reduce the availability of groundwater in the environment.